NASAB ANAK HASIL PERNIKAHAN SIRRI DALAM PERSPEKTIF FIQH DAN KOMPILASI HUKUM ISLAM (KHI) - Hanna, Siti; Ahmad, Lia Fauziyyah (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2024)
This article analyzes the fate of children resulting from unregistered marriages in a review of fiqh and the Compilation of Islamic Law (KHI). The sirr marriage polemic is closely related to the child's lineage status. Even though sirr marriages are carried out according to Islamic law, these marriages must be protected by State law in accordance with applicable laws and regulations to give them legal force, especially in relation to the child's lineage status. The aim of this research is to examine the lineage status of children from sirr marriages from the perspective of jurisprudence and the Compilation of Islamic Law. This research uses a qualitative descriptive approach to examine the lineage position of children born from sirr marriages. The results show that there are differences between fiqh and KHI regarding the fate of children born from sirr marriages. According to fiqh, all children born from marriages that fulfill the terms and conditions will be automatically assigned to their father. In jurisprudence, children born from unregistered marriages can be assigned to the father. However, in KHI, children born from unregistered marriages can be assigned to the father through a court order or istilhaq.